2019
DOI: 10.24093/awej/efl1.1
|View full text |Cite
|
Sign up to set email alerts
|

Studying Foreign Language Anxiety with its Causes and Effects: A case of King Khalid University EFL Learn

Abstract: The primary focus of the present study is to investigate the anxiety level of Saudi undergraduate students learning English as a Foreign Language (EFL). An attempt has been made to find out various possible causes, sources, and effects of foreign language anxiety on Saudi EFL learners. The study aims to answer the main question; if this anxiety affects the learning process of Saudi EFL learners positively or adversely. The study demonstrates some models and strategies related to causes and effects of anxiety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The study findings showed that most Saudi EFL college beginners experience a moderate level of FLA. This finding aligns with previous research findings (Mohammed, 2015;Alshahrani, 2016;Bhatti et al, 2016;Koka et al, 2019). They also revealed that gender did not affect FLA levels among EFL learners.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…The study findings showed that most Saudi EFL college beginners experience a moderate level of FLA. This finding aligns with previous research findings (Mohammed, 2015;Alshahrani, 2016;Bhatti et al, 2016;Koka et al, 2019). They also revealed that gender did not affect FLA levels among EFL learners.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Most of these issues are linked to factors that lead to increased fluency in English speaking and, as a result, improved language efficiency, especially when it comes to the question of learning English as a foreign language. Anxiety to speak English is one of the causes that has been identified as having an effect on language learners' success and, as a result, on language learning (Koka et al, 2019;Hussain et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of these issues are associated with the factors that result in better fluency in English speaking, leading to better performance in the language, particularly when it comes to the questioning of learning English as a foreign language. One factor that has been underlined to influence the performance of language learners, which in turn affects language learning and use, is anxiety to speak English (Limbago et al, 2019;Koka, Islam, and Osman, 2019).…”
Section: Introductionmentioning
confidence: 99%